2008
DOI: 10.1007/s00113-008-1488-7
|View full text |Cite
|
Sign up to set email alerts
|

Der Taylor Spatial Frame

Abstract: The main advantage of the TSF compared with other external frames is the ability to perform simultaneous correction of angular, axial, translational, and rotatory deformities. This enables a reduced correction time and increased patient comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Another possibility that may improve patient comfort or even make weight bearing possible for the patient is the application of a weight-bearing platform to the distal end of the frame in the case of a transfixed foot or soft tissue complications (Figure 1) [13,14]. Due to the modularity and variability of various frame mountings, which allow the orthopedic surgeon to adapt to any clinical situation, various frame configurations are in clinical use and exhibit good healing rates, but complications such as non- and mal-union continue to occur [15-18]. One cause of failure that may be detrimental to healing is the presence of excessive shear stresses produced by asymmetrical axial fracture site motion [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility that may improve patient comfort or even make weight bearing possible for the patient is the application of a weight-bearing platform to the distal end of the frame in the case of a transfixed foot or soft tissue complications (Figure 1) [13,14]. Due to the modularity and variability of various frame mountings, which allow the orthopedic surgeon to adapt to any clinical situation, various frame configurations are in clinical use and exhibit good healing rates, but complications such as non- and mal-union continue to occur [15-18]. One cause of failure that may be detrimental to healing is the presence of excessive shear stresses produced by asymmetrical axial fracture site motion [19,20].…”
Section: Introductionmentioning
confidence: 99%
“… 18 21 However, frequent frame modifications and the need for sequential correction of deformities during bone transport are the main limitations of the Ilizarov device. 5 , 22 , 23 One of the problems is that deformity or translation may occur during transport, particularly in cases with large defects. In such cases, the conventional monolateral rail fixator or classic Ilizarov fixator requires additional procedures or components for correction, depending on the degree of deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Good results were seen in approximately 80%, fair results in 8-15% and poor results in 9-13% after a mean follow-up of four years. With the availability of various ring configurations, new struts and a new foot programme, indications for treatment with TSF could be extended to severe foot deformities [5,20]. Eidelman et al [5] reported on 13 patients with various foot deformities.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that treatment using TSF is a powerful and accurate surgical modality for both limb and foot deformities. Seybold et al [20] also used the TSF to correct post-traumatic limb and foot deformities, concluding that the application of the TSF is simple and patients need a shorter stationary period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation